End of life care for people with alcohol and drug problems: Findings from a Rapid Evidence Assessment. (11th July 2019) - Witham, Gary; Galvani, Sarah; Peacock, Marian
Abstract: People who use alcohol and other drugs(hereafter "substances") and who are over the age of 40 are now more likely to die of a non‐drug related cause than people who use substances under the age of 40. This population will therefore potentially need greater access to palliative and end of life care services. Initially, the purpose of this rapid evidence assessment (REA), conducted August 2016–August 2017, was to explore the peer‐reviewed evidence base in relation to end of life care for people with problematic substance use. The following databases were searched using date parameters of 1 January 2004–1 August 2016: Amed, Psycharticles, Ovid, Ageinfo, Medline, Ebscohost, ASSIA, Social Care Online, Web of Knowledge, Web of Science, SSCI, Samsha, NIAAA. Data were extracted using a predefined protocol incorporating inclusion and exclusion criteria. Given the dearth of evidence emerging on interventions and practice responses to problematic substance use, the inclusion criteria were broadened to include any peer‐reviewed literature focussing on substance use specifically and end of life care. There were 60 papers that met the inclusion criteria. These were quality assessed. Using a textual thematic approach to categorise findings, papers fell into three broad groups (a) pain management, (b) homeless and marginalised groups, and (c) alcohol‐related papers. In general, this small and diverse literature lacked depth and quality. The papers suggest there are challenges for health and social care professionals in meeting the end of life needs of people who use substances. Addressing issues like safe prescribing for pain management becomes more challenging in the presence of substance use and requires flexible service provision from both alcohol/drug services and end of life care providers. Work is needed to develop models of good practice in working with co‐existing substance use and end of life conditions as well as prevalence studies to provide a wider context for policy development.